Precision DNA demethylation ameliorates disease in lupus-prone mice - Hao Li; Maria G. Tsokos; Sean Bickerton; Amir Sharabi; Yi Li; Vaishali R. Moulton; Philip Kong; Tarek M. Fahmy; George C. Tsokos (JCI Insight, 2018)
Defective DNA methylation in T cells leads to a series of T cell abnormalities in lupus; however, the full effect of T cell lineage–specific DNA methylation on disease expression has not been explored. Here, we show that 5-azacytidine, a DNA methyltransferase inhibitor, targeted to either CD4 or CD8 T cells in mice with established disease using a nanolipogel delivery system dramatically ameliorates lupus-related pathology through distinct mechanisms. In vivo targeted delivery of 5-azacytidine into CD4 T cells favors the expansion and function of Foxp3+ Tregs, whereas targeted delivery to CD8 T cells enhances the cytotoxicity and restrains the expansion of pathogenic TCR-αβ+CD4–CD8– double-negative T cells. Our results signify the importance of cell-specific inhibition of DNA methylation in the treatment of established lupus.